Pterophoridae (Lepidoptera) fauna of the Republic of Tuva - Ustjuzhanin, Peter; Rekelj, Jurij; Kovtunovich, Vasily; Ustjuzhanina, Anna (Zootaxa, 2017)
The present study gives a review of the Pterophoridae species recorded in the Republic of Tuva (Russia). 37 species of 17 genera are reported, new data on the distribution are provided, the distribution map of Pterophoridae in the Republic of Tuva is given, and Stenoptilia lasani Ustjuzhanin, Rekelj & Kovtunovich, sp. nov., is described.